Study of microstructural and electrical properties of silver substituted hydroxyapatite for drug delivery applications. (June 2022) - Chatterjee, Tuli; Ghosh, Moupiya; Maji, Moumita; Ghosh, Monidipa; Pradhan, Swapan Kumar; Meikap, Ajit Kumar
Abstract: Silver doped hydroxyapatites (Ag-HAp) [Ca10−x Agx (PO4 )6 (OH)2 ;(0.0 ≤x ≤ 1.0)] were synthesized with pH = 10, by the in-situ hydrothermal method. Structural, microstructural, compositional, electrical and biocompatibility properties of Ag-Hap samples were studied to ascertain the suitability of the experimental samples in drug-delivery applications. The Rietveld refinement of the X-ray diffraction (XRD) pattern, analysis of Fourier transform infrared (FTIR) spectra, X-Ray photoelectron (XPS) spectra, and Energy Dispersive X-Ray (EDAX) spectra of the Ag-HAp samples had confirmed the successful doping of Ag atoms in the HAp lattice and simultaneous growth of secondary β-TCP phase with the detailed chemical phase compositions of appropriate percentages. The Field Emission Scanning Electron Microscopy (FESEM), EDAX, and Brunauer–Emmett–Teller (BET) characterizations were carried out to study their morphological, compositional, surface, and porous behavior. The cytocompatibility of the laboratory-synthesized biomaterials with sensitive human embryonic kidney cells (HEK293) by in-vitro MTT assay testing revealed that the Ag-HAp powders had no toxic effect on living body-cells up to the safe limit of usage (≤15 μg/mL). The relative cell-viability percentage (%rcv) was evaluated to be 95–106% for highly doped samples. The incorporation of monovalent Ag ions within HAp lattice influenced the thermal hopping of the charge carriers and resulted in significantly high ionic conductivity with very low activation energy for higher temperatures. The significantly high dielectric permittivity for elevated temperatures (613 K) of the Ag-HAp compared to that of pure-HAp, and the considerable amount of interfacial polarization occurring within highly-conductive grain ( 10 −5 Sm −1 ) and resistive grain-boundary as established by complex impedance study gave rise to the probability of occurrence of the quasi-permanent surface potential with promising specific surface area ( 40 m 2 /g). The highly biocompatible Ag-HAp rods, with good dielectric and electrical properties, showed a huge possibility of the material being used as a nano-carrier for electric field-induced targeted drug delivery purposes in the future. Graphical Abstract: High dielectric nature can enhance electrical polarization useful for surface charge retention and possibility of strong electret formation which can help in electric field induced drug exchange for nano-carriers in targeted drug delivery. ga1 Highlights: Wide band semiconducting stoichiometric Ag doped HAp nanorods were synthesized. Anisotropic morphology with improved surface properties has been obtained. Enhanced permittivity and ionic conductivity improved cytocompatibility. High dielectric nature is useful for surface charge retention. Enhance electrical polarization useful for electret formation in targeted drug delivery.